Language and emotions in the Internet communication (a case study of commentaries in the YouTube services) - Burska, Katarzyna (Język(i) w czasie i przestrzeni, 2021)
The aim of this article is to present linguistic and paralinguistic ways of expression in Internet comments posted by YouTube users under the song Co mi, Panie, dasz, arranged by Adam Sztaba during the isolation caused by the coronavirus pandemic. Internet users emphasize the multitude of experiences that accompany them while playing the song, exposing positive feelings: pride, emotion, admiration, respect, gratitude, surprise. In order to express positive evaluation in the comments, lexical, word-formation and graphic measures as well as stylistic figures are used. They are used primarily for hyperbolization.